Movimentos pendulares das cidades polos paranaenses de Cascavel e Toledo : 2000 e 2010 - Schneider, Raquel Aline (2016)
The commuting is understood as carried out by individuals who reside in a municipality and work and/or study in another, allowing people to enter the labor market and/or improve their skills when they don t find the desired opportunities in the municipality in which reside. This work aimed to study the commuting of the cities of Cascavel and Toledo, poles of Western Paraná mesoregion in 2000 and 2010. Quantification and study of commuting are part of urban and regional planning and help identify the population amount that should be considered in the formulation of public policies. The data relating to commuting are extracted from Demographic Census microdata of 2000 and 2010 of Brazilian Institute of Geography and Statistics (IBGE). Thus, the commuting has a direct relationship with the economic dynamics of the region and the quality of life offered by them. The study showed that municipalities poles of Cascavel and Toledo are attractive, since it had greater input than output, both commuting workers and students. The intensity of the flows increased during the study period, indicating greater spatial population dynamics, since the fall of the participation of Curitiba (state capital) in commuting output of municipalities, together with the predominance of relationships, both commuting entry to the output of the closest cities - especially those belonging to own western Paraná - demonstrate the consolidation of the economic dynamics of the poles in the region and reflect the increase in the supply of jobs and vacancies in higher education. Regarding gender and age of individuals who traveled highlights the predominance of men in commuting to work, while women predominate in commuting to study. Overall individuals were young and single, but such characteristics declined during the period and, in 2010, there was increased participation of adult and elderly people and also married (especially regarding the purpose of work) in commuting. Another factor to be noted is that, with respect to Cascavel and Toledo outgoing mobility, the main motivator was the work, and with respect to incoming mobility, education has become the greatest motivation in 2010, which indicates the importance of higher education institutions of the municipalities and that they have also become educational centers, attracting students from throughout the region.